Improving Net Energy of Cumene Hydroperoxide Production using Cumene Oxidation Process Through Removing Cooler on the Recycle System to Achieve Energy Efficiency and Reduce Production Cost - Marpaung, Benaya Matius; Setyanto, Henricus Jovan; Aliyah, St Nur; Haryono, Lim Christoval Evandy (UPT Laboratorium Terpadu, Universitas Diponegoro, 2024)
This study investigates a modification to the cumene hydroperoxide (CHP) production process by removing the cooler between the reactor and separator, aiming to improve energy efficiency. The simulation results show that the modified process requires 245,259,223.09 kJ/h, compared to 265,992,099.05 kJ/h for the basic process, representing a significant energy reduction of 20,732,875.95 kJ/h. The removal of the cooler also leads to lower capital and operating costs, with annual savings of 111,900 in operating costs and 103,580 in utilities. This modification enhances the overall energy efficiency and cost-effectiveness of the CHP production process while maintaining product selectivity and operational performance. Copyright © 2024 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).